Development of a Clinical Prediction Rule for Venous Thromboembolism in Patients with Acute Leukemia - Al-Ani, Fatimah; Wang, Yimin Pearl; Lazo-Langner, Alejandro (Thrombosis and Haemostasis, 2020)
Risk factors for venous thromboembolism in patients with solid tumors are well studied; however, studies in patients with acute leukemia are lacking. We conducted a retrospective cohort study of adult patients diagnosed with acute myeloid leukemia and acute lymphoblastic leukemia diagnosed between June 2006 and June 2017 at a tertiary care center in Canada. Potential predictors of venous thromboembolism were evaluated using logistic regression and a risk score was derived based on weighed variables and compared using survival analysis. Internal validation was conducted using nonparametric bootstrapping. A total of 501 leukemia patients (427 myeloid and 74 lymphoblastic) were included. Venous thromboembolism occurred in 77(15.3%) patients with 71 events occurring in the first year. A prediction score was derived and validated and it included: previous history of venous thromboembolism (3 points), lymphoblastic leukemia (2 points), and platelet count > 50 × 109/L at the time of diagnosis (1 point). The overall cumulative incidence of venous thromboembolism was 44% in the high-risk group (≥ 3 points) versus 10.5% in the low-risk group (0–2 points) and it was consistent at different follow-up periods (log-rank p < 0.001). We derived and internally validated a predictive score of venous thromboembolism risk in acute leukemia patients.
Keywords: acute leukemia; venous thromboembolism; prediction; score